Democracy in Zuhud Concept: Politics of Articulation of Truth of Gus Mus’ Intelligence Practice in the 2015 NU Congress - Khoiron Khoiron; Purwo Santoso; Budi Irawanto (Political Science Program, Universitas Negeri Semarang, 2023)
This study describes intellectuality as a practice of contesting truth in offering alternative truths aside from the existing truth. This paper aimed to describe how the truth regime is articulated by the subject of knowledge and a political agent, namely Ahmad Mustofa Bisri, in the 2015 NU Congress. At that moment, Gus Mus’ practice of articulating truth by refusing the position of ‘rais aam’ was political. This study questioned how the regime of truth was articulated amid the power contest at the 2015 NU Congress. This study argued that, amid the practice of contesting truth, at the same time, there is a politics of value and idea articulation carried out by an individual who occupies a position as part of the intellectual. It is at the political level of the articulation of truth that novelty is described in this study. This study produced truths using text and context-based discourse analysis methods, including: 1). dismissing ‘hubbud dunya’, 2). fostering ‘mind’ and ‘morality’, and 3). it is strengthening ‘legawing ati’ in dedication. In contrast, the above markers are marker moments that reinforcer the primary marker, namely the regime of zuhud, articulated by Gus Mus by self-regulation (subject position) as ‘ a student’ related to elements of discourse antagonism—the term of ‘kiai’ related to the position of rais aam.